2012
DOI: 10.7324/japs.2012.2728
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Aqueous and Ethanolic Leaf Extracts of Cassia Alata Linn

Abstract: Cassia alata Linn is an important medicinal plant as well as ornamental flowering plant. The leaf decoction of Cassia alata has been used to treat infectious diseases in north eastern Nigeria. This study was embarked upon so as to evaluate the safety and efficacy of Cassia alata in the management of fungal infectious diseases. The leaves of the plant were collected, dried and extracted using water and 95% ethanol. The extracts were used for evaluating antifungal activity against five clinical isolates of patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 5 publications
2
31
0
4
Order By: Relevance
“…When comparing aqueous preparations of extracts to preparations using other organic solvents tested against B. cinerea, a parallel may be drawn between results from the present study and those achieved by Senhaji et al 27 , in that the present study revealed that complete (100%) mycelial inhibition could be achieved by using a 60% aqueous diluted extract (Table 1). Timothy et al 30 noticed a dose-dependent antifungal activity of leaf extracts of Cassia alata when tested against clinical isolates of pathogenic fungi, including a species of Penicillium. The same trend was noted in this study, with B. cinerea and P. expansum each eliciting a decrease in colony diameter with increasing concentration of garlic extract.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing aqueous preparations of extracts to preparations using other organic solvents tested against B. cinerea, a parallel may be drawn between results from the present study and those achieved by Senhaji et al 27 , in that the present study revealed that complete (100%) mycelial inhibition could be achieved by using a 60% aqueous diluted extract (Table 1). Timothy et al 30 noticed a dose-dependent antifungal activity of leaf extracts of Cassia alata when tested against clinical isolates of pathogenic fungi, including a species of Penicillium. The same trend was noted in this study, with B. cinerea and P. expansum each eliciting a decrease in colony diameter with increasing concentration of garlic extract.…”
Section: Discussionmentioning
confidence: 99%
“…albicans 100 mg/mL (Hassawi and Kharma, 2006) Achillea fragantissima C. albicans 150 mg/mL (Hassawi and Kharma, 2006) Acorus calamus C. albicans 28.80 mg/mL (Thirach et al, 2003) Adiantum capillus veneris C. albicans 1 mg/mL * (Ishaq et al, 2014) Allium cepa C. albicans 10 mg/mL * (Doddanna et al, 2013) Allium sativum C. albicans 1 mg/mL * (Wong and Tsang, 2009) Anthemis pseudocotula C. albicans 150 mg/mL (Hassawi and Kharma, 2006) Artemisia herba-alba C. albicans 100 mg/mL (Hassawi and Kharma, 2006) Ballota undulate C. albicans 25 mg/mL (Hashem, 2011) Camellia sinensis C. albicans 10 mg/mL * (Doddanna et al, 2013) Capparis spinosa C. albicans 100 mg/mL * (Mandeel and Taha, 2005) Capsicum annum C. albicans 17.5 mg/mL (Ertürk, 2006) Cassia alata C. albicans 5.60 mg (Timothy et al, 2012) Cassia siamea C. albicans 100 mg/mL C. glabrata 100 mg/mL C. guilliermondii 100 mg/mL C. krusei 100 mg/mL C. parapsilosis 100 mg/mL C. tropicalis 100 mg/mL Caulerpa scalpelliformis C. albicans 100 mg/mL C. glabrata 100 mg/mL C. guilliermondii 100 mg/mL C. krusei 100 mg/mL C. parapsilosis 100 mg/mL C. tropicalis 100 mg/mL …”
Section: Achillea Biebersteiniimentioning
confidence: 99%
“…The observed analgesic activities of P. guajava may be due mainly to quercetin, flavonoid and steroids contained in this plant 28 . Previous reports demonstrated that the leaves of Psidium guajava and some medicinal plant like Cassia alata are rich in flavonoids, in particular, quercetin which may be responsible for their therapeutic activity [29][30] .…”
Section: Discussionmentioning
confidence: 99%